Rapid Quantitation of Furanocoumarins and Flavonoids in Grapefruit Juice using Ultra Performance Liquid Chromatography - VanderMolen, Karen M. (2013)
INTRODUCTION: Grapefruit juice can increase or decrease the systemic exposure of myriad oral medications, leading to untoward effects or reduced efficacy. Furanocoumarins in grapefruit juice have been established as inhibitors of cytochrome P450 3A (CYP3A)-mediated metabolism and P-glycoprotein (P-gp)-mediated efflux, while flavonoids have been implicated as inhibitors of organic anion transporting polypeptide (OATP)-mediated absorptive uptake in the intestine. The potential for drug interactions with a food product necessitates an understanding of the expected concentrations of a suite of structurally diverse and potentially bioactive compounds. OBJECTIVE: Develop methods for the rapid quantitation of two furanocoumarins (bergamottin and 6′,7′-dihydroxybergamottin) and four flavonoids (naringin, naringenin, narirutin, and hesperidin) in five grapefruit juice products using ultra performance liquid chromatography (UPLC). METHODOLOGY: Grapefruit juice products were extracted with ethyl acetate; the concentrated extract was analyzed by UPLC using acetonitrile:water gradients and a C18 column. Analytes were detected using a photodiode array detector, set at 250 nm (furanocoumarins) and 310 nm (flavonoids). Intraday and interday precision and accuracy and limits of detection and quantitation were determined. RESULTS: Rapid (<5.0 min) UPLC methods were developed to measure the aforementioned furanocoumarins and flavonoids. R(2) values for the calibration curves of all analytes were >0.999. Considerable between-juice variation in the concentrations of these compounds was observed, and the quantities measured were in agreement with the concentrations published in HPLC studies. CONCLUSION: These analytical methods provide an expedient means to quantitate key furanocoumarins and flavonoids in grapefruit juice and other foods used in dietary substance-drug interaction studies.